Autoimmune thyroid disease modifies the clinical expression of hand osteoarthritis in older people: a third National Health and nutrition examination survey study - Tagoe, Clement E.; Wang, Wanyi; Kwon, Helena H. (Frontiers in Medicine, 2024)
Introduction The risk factors linked to hand osteoarthritis (OA) that contribute to its distinct symptoms and clinical presentation are not thoroughly understood. This study aimed to examine whether the autoimmune thyroid disease (AITD) autoantibodies, anti-thyroid peroxidase antibody (TPOAb), and anti-thyroglobulin antibody (TgAb), associate with hand OA and symptomatic hand OA in the Third National Health and Nutrition Examination Survey (NHANES III). Materials and methods We included 2,429 persons from NHANES III ≥60 years of age. Data on hand OA or symptomatic hand OA were examined with respect to their associations with TPOAb and TgAb. Log-binomial and modified Poisson regression models were fit to examine the associations between the anti-thyroid autoantibodies and hand OA or symptomatic hand OA. Results Higher levels of TPOAb were associated with a higher prevalence of symptomatic hand OA in the unadjusted (PR = 1.182, p = 0.024) and adjusted models after controlling for age, gender, and diabetes (PR = 1.174, p = 0.039). This association was no longer significant when positive TPOAb was considered a categorical variable with four levels and compared with negative TPOAb. TgAb showed a trend toward being positively associated with symptomatic hand OA (p < 0.10). When positive TgAb was considered a categorical variable with four levels and compared with negative TgAb, the highest quartile was associated with a higher prevalence of symptomatic hand OA than negative TgAb in the unadjusted (PR = 2.242, p = 0.008) and adjusted models (PR = 2.045, p = 0.038). There was no significant association between TPOAb or TgAb and hand OA. Conclusion Higher levels of TPOAb may be associated with the presence of symptomatic hand OA in persons ≥60 years old. Persons ≥60 years old with the highest quartile levels of TgAb may be more likely to present with symptomatic hand OA.